2021
DOI: 10.1101/2021.10.07.463592
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive antibody profiling of mRNA vaccination in children

Abstract: With the emergence of SARS-CoV-2 variants, fluctuating mask mandates, and school re-openings, increased infections and disease surged among children recently. Thus, there is an urgent need for COVID-19 vaccines for children of all ages. However, whether young children will respond appropriately to mRNA vaccines remains unclear. Here, we deeply profiled the vaccine-induced humoral immune response in 7-11 year old children receiving the mRNA-1273 vaccine. Vaccinated children induced significantly higher antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Therefore, dose finding is crucial, particularly in vulnerable infants. For example, recent data on SARS-CoV2 mRNA vaccination with Comirnaty demonstrate that dose adjustments to 30 µg have resulted in poor immunogenicity in children under 5 years [138]. Most importantly, the potential future use of mRNA vaccines in vulnerable preterm infants must be above any safety concerns [136].…”
Section: Novel Vaccines: Mrna Technologymentioning
confidence: 99%
“…Therefore, dose finding is crucial, particularly in vulnerable infants. For example, recent data on SARS-CoV2 mRNA vaccination with Comirnaty demonstrate that dose adjustments to 30 µg have resulted in poor immunogenicity in children under 5 years [138]. Most importantly, the potential future use of mRNA vaccines in vulnerable preterm infants must be above any safety concerns [136].…”
Section: Novel Vaccines: Mrna Technologymentioning
confidence: 99%
“…Encouragingly, the immune responses that have been generated display sufficient cross-coverage of the VOC, Omicron, with comparable immune responses to those reported in adults 8 . This could suggest that children develop a similar adaptive humoral immune response as seen in adults 9 , which may provide benefits to children as additional variants of concern emerge. While it is plausible that vaccine-induced anamnestic immunity may provide some level of protection in this population upon exposure, the durability of vaccine-induced immunity wanes in adolescents, and boosting may promote a robust barrier of immunity that will contribute to public health efforts to limit spread and prevent future hospitalizations and severe disease.…”
Section: Discussionmentioning
confidence: 98%
“…Cross-VOC antibody responses were observed at 50 and 100 μg vaccination, and humoral immunity to Omicron was observed at 100 μg vaccination. 171 Convalescent children who have been infected with SARS-CoV-2 and children vaccinated with two doses of BNT162b2 have reduced sensitivity to serum antibodies against the Omicron variants and have been more vulnerable to breakthrough infection. 131 A retrospective study conducted live virus and pseudovirus neutralization tests on the Omicron variant showed that the neutralizing effect of Omicron (B.1.1.529) variant decreased in serum from people who were vaccinated with BNT162b2 vaccine, mRNA-1273 vaccine, Sinopharm BBIBP-CorV vaccine, and the neutralizing activity against Omicron increased after booster vaccination.…”
Section: Omicron Variants Along With the Protective Effect Of Vaccinesmentioning
confidence: 99%
“…One study showed different responses in children (6–11 years old) vaccinated with varying doses of mRNA vaccines. Cross‐VOC antibody responses were observed at 50 and 100 μg vaccination, and humoral immunity to Omicron was observed at 100 μg vaccination 171 . Convalescent children who have been infected with SARS‐CoV‐2 and children vaccinated with two doses of BNT162b2 have reduced sensitivity to serum antibodies against the Omicron variants and have been more vulnerable to breakthrough infection 131 …”
Section: Prophylaxis and Treatment Of Omicron Variantmentioning
confidence: 99%